Rotating Stall in Centrifugal Compressor Vaneless Diffuser: Experimental Analysis of Geometrical Parameters Influence on Phenomenon Evolution. (2004) - Ferrara, Giovanni; Ferrari, Lorenzo; Baldassarre, Leonardo
Abstract : The rotating stall is a key problem for achieving a good working range of a centrifugal compressor and a detailed understanding of the phenomenon is very important to anticipate and avoid it. Many experimental tests have been planned by the authors to investigate the influence on stall behavior of different geometrical configurations. A stage with a backward channel upstream, a 2-D impeller with a vaneless diffuser and a constant cross-section volute downstream, constitute the basic configuration. Several diffuser types with different widths, pinch shapes, and diffusion ratios were tested. The stage was instrumented with many fast response dynamic pressure sensors so as to characterize inception and evolution of the rotating stall. This kind of analysis was carried out both in time and in frequency domains. The methodology used and the results on phenomenon evolution will be presented and discussed in this article.